Lifestyle intervention and cognitive outcomes in Down syndrome: a horizon 21 European Down syndrome consortium scoping review - Eustace-Cook, Jessica; Mc Glinchey, Eimear (My University, 2026)
Background: Life expectancy for individuals with Down syndrome (DS) has significantly increased, primarily due to medical advances. While DS is considered a genetically determined form of Alzheimer's disease (DS-AD), with neuropathological markers evident by age 40, the onset of clinical dementia varies. Modifiable risk factors are thought to contribute meaningfully to dementia risk in the general population. Advances in intervention studies in the general population suggest cognitive decline can be reduced through multimodal lifestyle interventions, however no large-scale multimodal studies have been conducted in the DS population. Search Strategy: A comprehensive search was conducted across five electronic databases—Medline, EMBASE, CINAHL, Web of Science, and ASSIA to identify studies that examined the relationship between lifestyle interventions and cognitive outcomes in adults with DS. The search combined database-specific controlled language with keywords related to exercise, diet, social activities, cardiovascular health, and brain stimulation. Studies included were peer-reviewed original research articles focusing on adults with DS and reported on cognitive outcomes or AD-related biomarkers. Results: The search yielded 24,774 articles, with 16,868 remaining after duplicates were removed. A total of 44 articles met inclusion criteria across the domains of exercise, diet, cardiovascular health, social connectedness, and cognitive stimulation. Most studies focused on exercise, indicating some cognitive benefits, particularly in executive functions and working memory, though results were inconsistent, and many suggested the necessity of high adherence to intervention protocols. No studies were found that examined the direct impact of diet on cognition in DS. Findings on cognitive stimulation, cardiovascular health and social connectedness suggested potential but inconclusive benefits for cognitive function. Conclusions: This review underscores the significant gaps in research regarding non-pharmacological interventions for DS-AD. It highlights the need for tailored, well-structured studies to better understand and leverage potential cognitive benefits of lifestyle interventions in the DS population. Implementing such interventions early in life and before significant disease progression may help maintain quality of life and independence among individuals with DS. Future research should focus oncomprehensive, multi-domain interventions to ascertain their efficacy and optimal application.
PUBLISHED
Keywords: Down Syndrome; Cognitive Decline; Lifestyle Interventions; Non-Pharmacological Strategies; Dementia Prevention; Modifiable Risk Factors; Alzheimer's Disease; Ageing; Cancer; Inclusive Society